Completer :

F = (... + 6) ²

= x² + 2 x ....... x .. + ...........²

= ....... + ........... + ........

G = (y - ..)²

= ...... - 2 x ...... x ........ + .......²

= ........ - 10y + ............

K= (...+10)(..... - ......)

= x² - ....²

= ....... - ........

2

Réponses

2012-11-22T19:07:30+01:00

Bonsoir,

 

F = (x + 6) ²

       = x² + 2 fois x fois  6+ 6²

       = x² + 12x + 36

 

Fais de même pour les autres, car c'est la même principe ! ;)

2012-11-22T19:11:18+01:00

Bonjour,

 

F = (x + 6) ²

       = x² + 2 x 6 x  + 6²

       = x² + 12x + 36

 

G = (y - 5)²

     =y² - 2 x5 x y +5²

    = y² - 10y + 25

 

K= (x+10)(x - 10)

   = x² - 10²

 = x² - 100

 

J'espère que tu as compris

 

A+